Capitalism and Corporate in Lampung Local Politics - Kurniawan, Robi Cahyadi; Hermawan, Dedy; Indrajat, Himawan; Kurniawan, Budi (Universitas Negeri Semarang, 2019)
State and company / corporation in the context of governance are two of the three fundamental pillars of democratic development in addition to the market . The relation of both, in the context of Lampung's local politics is object to study, in particular the company /SGC. This research was conducted in May 2014. The study used a qualitative research type, which saw most of the intrinsic social life, with in-depth interviews with personalities and selected informants. The approach used in this study is the approach of critical social science (CSS), which saw social science as a process of critical inquiry phenomenon. The results showed that in Lampung local election at 2014 ago, there were strong relations between the corporation / company in the case of the Sugar Group Company (SGC) in the Lampung Governor candidates. SGC is serving as a source of funding for the campaign of the election for the last governor election in 2014. SGC does it as a way of business development.